Energy-based design of elastic joints for inverted pendulum systems with input saturation - Franco,E (IEEE, 2019)
This work investigates the balancing control of underactuated inverted pendulum systems with input saturation. To this end, the design of elastic joints according to potential-energy shaping principles is combined with energy-shaping control. As a result, analytical design guidelines are synthesized and implemented fortwo classical examples: the inertia-wheel pendulum and the Acrobot system.Asimulation study demonstrates the effectiveness of the proposed approach in reducing control effort while preserving transient performance.